1996
DOI: 10.1007/bf00029982
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of the root-inhabiting fungi, Fusarium, Cylindrocarpon and Pythium, on container-grown Douglas-fir and spruce seedlings in British Columbia

Abstract: Application.Species of Fusarium, Cylindrocarpon or Pythium were readily isolated from the roots and growth medium of container-grown Douglas-fir and spruce seedlings. Differences in their occurrence varied with nursery, but not consistently with conifer species, indicating that cultural practices which alter conditions such as growth medium moisture and temperature can influence their prevalence.Abstract. Surveys were made at the end of the 1990 and 1991 growing seasons for rootinhabiting fungi in the genera F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The authors note that soil-borne pathogens were commonly enhanced in 83% of the studies they reviewed, but foliar pathogens were enhanced in only 33% of the studies. For forest nurseries in western North America, soil-borne pathogens (i.e., Cylindrocarpon, Fusarium, and Pythium) are ubiquitous (e.g., [66]), but the expression of disease is usually only associated with prolonged, excessive moisture in the growing media (e.g., [66][67][68][69]) often due to excessive irrigation. In addition, the basal portion of all containers, post irrigation, experience saturated conditions for some duration, which is a function of plant phenology, container height, and medium porosity [60].…”
Section: Discussionmentioning
confidence: 99%
“…The authors note that soil-borne pathogens were commonly enhanced in 83% of the studies they reviewed, but foliar pathogens were enhanced in only 33% of the studies. For forest nurseries in western North America, soil-borne pathogens (i.e., Cylindrocarpon, Fusarium, and Pythium) are ubiquitous (e.g., [66]), but the expression of disease is usually only associated with prolonged, excessive moisture in the growing media (e.g., [66][67][68][69]) often due to excessive irrigation. In addition, the basal portion of all containers, post irrigation, experience saturated conditions for some duration, which is a function of plant phenology, container height, and medium porosity [60].…”
Section: Discussionmentioning
confidence: 99%
“…Before the molecular era, our knowledge about ECM fungal communities in forest nurseries was mainly based on morphotyping (morphological and anatomical identification) of mycorrhizal root tips [32][33][34], fungal isolation [35,36], or a combination of both of these methods [37,38]. Significant advances have been made since it was demonstrated that direct sequencing of fungal DNA from root tips could be a powerful and sensitive tool for the identification of potentially all root-inhabiting fungi [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…1989). Although there is a substantial amount of information on incidence of root pathogens in forest nurseries (Galaaen and Venn 1979; Kope et al. 1996; Lilja et al.…”
Section: Introductionmentioning
confidence: 99%